(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article examines the problems of designing and organizing the urban ecological environment. The article deals with some current problems related to the lack of landscape environments in cities, as well as considers modern methods of beautification of areas in this area. The established principles of landscape design can be used in the educational process of universities where this course is available during the professional training of future landscape designers.